2012
DOI: 10.3390/cancers4041318
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Synergistically Enhances Anti-Proliferative Activity of Vincristine in Cervical and Gastric Cancer Cells

Abstract: In this study, the anti-proliferative and anticancer activity of azithromycin (AZM) was examined. In the presence of AZM, cell growth was inhibited more effectively in Hela and SGC-7901 cancer cells, relative to transformed BHK-21 cells. The respective 50% inhibition of cell growth (IC50) values for Hela, SGC-7901 and BHK-21 were 15.66, 26.05 and 91.00 µg/mL at 72 h post incubation, indicative of a selective cytotoxicity against cancer cells. Cell apoptosis analysis using Hoechst nuclear staining and annexin V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The biocompatibility of AZI-liposomes (CL-3, PGL-2 and DPGL-2) was investigated in vitro to determine the possible cytotoxic effects of the liposome constituents and AZI toward human cervical cells (HeLa cells). It was reported that AZI can synergistically enhance the antiproliferative activity of vincristine in cancer cells 54. Furthermore, recent findings demonstrated that free AZI was cytotoxic to human fibroblasts at a concentration of 16 µg/ml (49% viability) and human keratinocytes at 64 µg AZI/ml (55% viability), while entrapment of AZI in liposomes significantly decreased skin cell cytotoxicity 17…”
Section: Resultsmentioning
confidence: 98%
“…The biocompatibility of AZI-liposomes (CL-3, PGL-2 and DPGL-2) was investigated in vitro to determine the possible cytotoxic effects of the liposome constituents and AZI toward human cervical cells (HeLa cells). It was reported that AZI can synergistically enhance the antiproliferative activity of vincristine in cancer cells 54. Furthermore, recent findings demonstrated that free AZI was cytotoxic to human fibroblasts at a concentration of 16 µg/ml (49% viability) and human keratinocytes at 64 µg AZI/ml (55% viability), while entrapment of AZI in liposomes significantly decreased skin cell cytotoxicity 17…”
Section: Resultsmentioning
confidence: 98%
“…A CDI value <1, =1 or >1 indicates that the drugs are synergistic, additive or antagonistic, respectively. A CDI value less than 0.7 indicates that the drugs are significantly synergistic [46,47].…”
Section: Methodsmentioning
confidence: 99%
“…Azithromycin accumulates and undergoes slow release in cells, especially in phagocytes, and thus has higher local concentration and longer half-life than older macrolides (i.e., erythromycin and clarithromycin) [ 1 , 2 ]. Recent studies have indicated that azithromycin could produce potent anti-proliferation effect by inducing apoptosis in HeLa cells and SGC-7901 cancer cells [ 3 ]. Clinical studies have suggested promising efficacy of azithromycin in combination with paclitaxel and cisplatin in stage III–IV NSCLC patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%